Kadar Pestisida Orgonofosfat Dalam Tumbuhan Kangkung (Ipomoea aquatica) Di Lahan Pertanian - Chesya P.R. Salindeho; Odi Roni Pinontoan; Finny Warouw (Universitas Sam Ratulangi, 2020)
Background: Pesticide is a chemical substance used to kill pests, in the form of plants, insects, and animals in our circled animal that has a health impact for humans either directly exposed or consuming food in the form of vegetables-vegetables. So in the regulation of the Minister of Agriculture number 07/Permentan/SR. 140/2/2007 concerning the requirements and procedures for the Registration of Pesticides, pesticides are chemicals or other substances and bodies renic and viruses. This research aims to know how much residual pesticide levels of orgonophosphate in plants in the agricultural land Mahena subdistrict Tahuna. Method: Research method, this research is a quantitative research laboratory based. The research was conducted in September 2019 until October 2019. Sampling in this research is taken from 4 locations with a total of 4 sanpel in the farm land Mahena subdistrict Tahuna. Result: The results of this study using the maximum residue limit (BMR) with the type of pesticide insecticide active ingredient Dimacide 400 EC showed that the average value of laboratory test Results Location 1 (0.63014), location 2 (0.1464), location 3 (0.28339), location 4 (0.0137) can still be tolerated with a maximum residue limit. The results of this research are based on laboratory test faculty of MIPA UNSRAT. Conclusion: The results of this research can be concluded that to 4 samples of the level of pesticides orgonophosphate still meet the requirements of the maximum residue type of vegetables Kangkung in Menkes No 39 Tahuna 2015 because less than 1 ppm.